Penicillin G-Induced Chlamydial Stress Response in a Porcine Strain of Chlamydia pecorum - Cory Ann Leonard; Frederic Dewez; Nicole Borel (International Journal of Microbiology)
Chlamydia pecorum causes asymptomatic infection and pathology in ruminants, pigs, and koalas. We characterized the antichlamydial effect of the beta lactam penicillin G on Chlamydia pecorum strain 1710S (porcine abortion isolate). Penicillin-exposed and mock-exposed infected host cells showed equivalent inclusions numbers. Penicillin-exposed inclusions contained aberrant bacterial forms and exhibited reduced infectivity, while mock-exposed inclusions contained normal bacterial forms and exhibited robust infectivity. Infectious bacteria production increased upon discontinuation of penicillin exposure, compared to continued exposure. Chlamydia-induced cell death occurred in mock-exposed controls; cell survival was improved in penicillin-exposed infected groups. Similar results were obtained both in the presence and in the absence of the eukaryotic protein translation inhibitor cycloheximide and at different times of initiation of penicillin exposure. These data demonstrate that penicillin G induces the chlamydial stress response (persistence) and is not bactericidal, for this chlamydial species/strain in vitro, regardless of host cell de novo protein synthesis.